Football players point causal reasoning and its relationship to the motivation of achievement, in sports competition. - Kerarma, Ahmed; Seghir, Noureddine (Journal of Human Sciences, 2021)
This study aimed to identify the direction of the causal explanation towards both attribution of the result or attribution of performance and their relationship to the level of achievement motivation. The results came to confirm that the studied sample is distinguished by an internal destination in attribution of victory dimension and attribution of good performance dimension, and an external destination in attribution of defeat dimension and poor performance. They attribute the failure to unstable external factors; difficult to control. Also, the owners of the internal destination for the dimensions of the causal reason are distinguished by a higher level of achievement motivation compared to the owners of the external destination. In addition the existence of positive direct relationship between the internal destination of the dimensions of causal explanation and the level of achievement motivation, and inverse between the external destination and the level of achievement motivation.